1981
DOI: 10.1007/bf00252688
|View full text |Cite
|
Sign up to set email alerts
|

Wound healing in normal and diabetic Chinese hamsters

Abstract: Summary.Wound healing was examined in normal and diabetic, non-ketotic Chinese hamsters by morphological and morphometric methods. Dermal, perforating wounds were made in the ears of the hamsters and the response to injury was evaluated in tissue biopsies. The response in normal hamsters was characterized by vascular and cellular migration and pronounced infiltration of polymorphonuclear leukocytes into the area closest to the wound (zone 1). The transition region (zone 2) between wounded and non-wounded tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
1

Year Published

1982
1982
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…Specifically, leukocyte infiltration [28,29] and the inflammatory phase of wound healing are disturbed [28][29][30][31] leading to abnormal tissue repair in diabetics. In addition, some experiments have shown that factors in diabetic serum inhibit leukocyte chemotaxis in vivo [32] and collagen synthesis in vitro [33].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, leukocyte infiltration [28,29] and the inflammatory phase of wound healing are disturbed [28][29][30][31] leading to abnormal tissue repair in diabetics. In addition, some experiments have shown that factors in diabetic serum inhibit leukocyte chemotaxis in vivo [32] and collagen synthesis in vitro [33].…”
Section: Discussionmentioning
confidence: 99%
“…128 -129 Also, wound healing of diabetic Chinese hamsters was characterized by increased edema with delayed and reduced vascular and cellular infiltration in the early healing period. 130 Diabetic Chinese hamsters have also been reported to have significantly increased numbers of somatotrophs which could produce hormonal antagonists to insulin. 131…”
Section: Morphologic Changes and Complicationsmentioning
confidence: 99%
“…On the basis of these studies, we suggest that the defect in cellular proliferation in diabetes mellitus is due to depletion of circulating growth factors other than insulin and somatomedins. (Endocrinology 112: 1026,1983) I NSULIN-deficient diabetes mellitus is characterized by growth retardation, weight loss, tissue atrophy, impaired wound healing, and impaired lymphocyte blast transformation (1)(2)(3). Similar features are seen in experimentally induced diabetes in the rodent (4)(5)(6).…”
mentioning
confidence: 92%
“…Proliferation of mesenchymal bone precursor cells has been shown to be impaired in streptozotocin-treated diabetic rats (12). Furthermore, fibroblast and vascular proliferation after dermal injury are reduced in spontaneously diabetic hamsters (3). These in vivo observations may result from the depletion of circulating growth factors necessary for cell proliferation, the presence of an inhibitor of cell division, or both in untreated diabetes.…”
mentioning
confidence: 97%